THE ROLE OF FATHERS IN BREASTFEEDING - Déa Silvia Moura da Cruz; Isa Nery Silva Batista dos Santos Rocha; Daniela Karina Antão Marques; Ilana Vanina Bezerra de Souza (Universidade Federal do Paraná, 2011)
Considering the importance of breastfeeding, the necessity arose of investigating the fathers' participation in, and perception of, breastfeeding. This exploratory-descriptive research with a qualitative approach was carried out in the Frei Damião Maternity Hospital in the county of João Pessoa-PB with ten fathers in April 2011. It was observed that the majority of the fathers were quite interested in and committed to carrying out this new task of helping their wives, as they knew the advantages of breastfeeding. Some of them however did not have this knowledge and equally did not include themselves in breastfeeding, saying it was a moment for the mother and baby alone. There is a necessity for fathers to be included in health education activities taking place in the pre- and post-birth periods and those which follow in child-rearing, as caring for a baby is the responsibility of the couple.